Addressing antimicrobial resistance in China: policy implementation in a complex context. Issue 1 (December 2016) - Wang, Li; Zhang, Xiulan; Liang, Xiaoyun; Bloom, Gerald
Abstract The effectiveness of antibiotics in treating bacterial infections is decreasing in China because of the widespread development of resistant organisms. Although China has enacted a number of regulations to address this problem, but the impact is very limited. This paper investigates the implementation of these regulations through the lens of complex adaptive systems (CAS). It presents the findings from reviews of relevant policy documents and published papers. The paper identifies different types of agent and explores their interaction with regard to the use of antibiotics and their responses to changes of the regulations. It focuses particularly on the impact of perverse financial incentives on overall patterns of use of antibiotics. Implications for the possibilities of nonlinear results, interactive relationships, and new pathways of policy implementation are discussed. The paper concludes that policy-makers need to better understand the objectives, incentives and potential adaptive behaviors of the agents when they implement interventions to improve antibiotic use and reduce the risk of emergence of resistant organisms.